(3aGJMI GdYdhes - (3eMeO Hf eMeO Hf eMeO GdZRGdj GdTGaYj GdWhSj , CHh MGeO, MLI GdGSdGe GdZRGdj,J (B505 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi HPcQg jaJJM cd cJGH aCLHfG GdEbJOGA Hg hUOQfG GdYdhe HcJGH SejfGg aGJMI GdYdhe fPcQ ajgG TQGFW GdYde haVGFdI hdhGReI hjfcTa ai SHYI CHhGH GdHGH GdChd ai aVjdI GdYde s
(3BNQgG (B:s
(3hbGd WGFaI HhLhHg hCf GdfXQ hGdHMK ajg MQGeGJ hjdRe GdJbdjO ZjQ GdeLJgO hEf cGf YGdekG HHYV GdYdhe GdeYJHQI ai GdELJgGO hfMeO Gddg Ydi EJeGe eG CQOJg s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B22 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B266 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B2 - (3U (B79s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1214s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdadSaI hGdefWbs